Taxes as instruments of public policy - Sproule-Jones, Mark, 1941-; Maslove, Allan M.; Ontario. Fair Tax Commission (Toronto : Published by University of Toronto Press in cooperation with the Fair Tax Commission of the Government of Ontario, 1994)
Taxes are not only a means of raising revenues. Governments also use taxes as instruments to achieve other economic and social policy goals. The role of the user fees to achieve greater efficiency in the production and consumption of publicly provided goods and services is the subject of the first paper in this volume. The following two papers discuss the role of the tax system in human capital investment and the feasibility and impact of a carbon/energy tax, addressing an important concern of environmental policy. The final paper identifies and estimates existing tax expenditures in the Ontario tax system and discusses the implications of these tax measures.
Foreword / Monica Townson -- Introduction / Allan M. Maslove -- 1. User Fees / Mark Sproule-Jones -- 2. Tax Treatment of Human Capital / Morley Gunderson and Wayne R. Thirsk -- 3. The Economic Effects of an Environment Tax / Arthur Donner and Fred Lazar -- 4. Ontario Tax Expenditures / Sheila M. Block and Allan M. Maslove.
Includes bibliographical references.
Electronic reproduction.
Master and use copy. Digital master created according to Benchmark for Faithful Digital Reproductions of Monographs and Serials, Version 1. Digital Library Federation, December 2002.
digitized
Print version record.
JSTOR
Keywords: Taxation -- Ontario; Political planning -- Ontario; Impôt -- Ontario; Politique publique -- Ontario; BUSINESS & ECONOMICS -- Economics -- Macroeconomics; POLITICAL SCIENCE -- Economic Conditions; BUSINESS & ECONOMICS -- Taxation -- General; Political planning; Taxation; Ontario; Steuerpolitik; Aufsatzsammlung; Taxation; Ontario